Square Waveguide Polarizer with Diagonally Located Irises for Ka-Band Antenna Systems - Piltyay, S. (Advanced Electromagnetics, 2021)
This article presents the results of development and optimization of a new square waveguide polarizer with diagonally located square irises. The application of suggested geometrical modification of irises form and location instead of a standard wall-to-wall irises configuration allows to exclude 45-degree twists between wideband waveguide polarizer and orthomode transducer of a dual-polarized antenna feed system. In addition, a waveguide polarizer and polarization duplexer can be manufactured by milling technology as two single details, which makes the proposed engineering solution reliable, simple for simulation, development and application. Suggested new polarizer design was developed for the satellite operating Ka-band. It contains 12 irises, which are symmetrically located in the diagonal corners of a square waveguide. Obtained optimal polarization converter provides excellent matching and polarization performance. The maximum level of VSWR is less than 1.04 for both orthogonal polarizations. Values of cross-polarization discrimination are higher than 32 dB in the operating Ka-band. Developed square waveguide polarizer with diagonally located irises can be applied in modern wideband satellite antennas.